(untitled) (LEGAL DIALOGICA, 2025)
This research aims to explore and explain the effectiveness of handling criminal acts of prostitution involving children as well as the investigative efforts carried out by the police in eradicating this problem. The Makassar Police investigation team has carried out prevention through regular investigations and provided complaint services through shelters. The method used in this research is empirical law, with the research location at the Makassar City Police Department. Data was collected using interview techniques and literature study, which was then analyzed qualitatively and descriptively. The research results show that there are challenges in handling cases of criminal acts of prostitution against children. The investigation process adheres to Article 2 paragraphs (1) and (2) and Article 761 of Law no. 35 of 2014 concerning amendments to Law no. 23 of 2002 concerning child protection. However, weak law enforcement against perpetrators of child prostitution means they feel safe and are not afraid of facing the legal process. Based on these findings, it is recommended that Makassar City Resort police investigators increase supervision and carry out outreach to the community. This is important so that they can be more aware of pimps who target children around them, as well as provide an understanding of the laws that apply to catch pimps and protect children who are victims of prostitution. Abstrak: Penelitian ini bertujuan untuk mengeksplorasi dan menjelaskan efektivitas penanganan tindak pidana prostitusi yang melibatkan anak-anak serta upaya penyidikan yang dilakukan oleh kepolisian dalam memberantas permasalahan tersebut. Tim penyidik Polrestabes Makassar telah melakukan pencegahan melalui penyidikan secara berkala dan menyediakan layanan pengaduan melalui tempat penampungan (shelter). Metode yang digunakan dalam penelitian ini adalah hukum empiris, dengan lokasi penelitian di Kepolisian Resor Kota Makassar. Data dikumpulkan dengan teknik wawancara dan studi pustaka, yang selanjutnya dianalisis secara kualitatif dan deskriptif. Hasil penelitian menunjukkan adanya tantangan dalam menangani kasus tindak pidana prostitusi terhadap anak. Proses penyidikan berpegang pada Pasal 2 ayat (1) dan (2) serta Pasal 761 UU No. 35 Tahun 2014 tentang perubahan UU No. 23 Tahun 2002 mengenai perlindungan anak. Namun, lemahnya penegakan hukum terhadap pelaku prostitusi anak menyebabkan mereka merasa aman dan tidak takut menghadapi proses hukum. Berdasarkan temuan tersebut, disarankan agar penyidik kepolisian Resor Kota Makassar meningkatkan pengawasan dan melakukan sosialisasi kepada masyarakat. Hal ini penting agar mereka dapat lebih waspada terhadap oknum-oknum mucikari yang menargetkan anak-anak di sekitar mereka, serta memberikan pemahaman mengenai hukum yang berlaku untuk menjerat mucikari dan melindungi anak-anak yang menjadi korban prostitusi.